Interaksi Simbolik Siswa SMAN 1 Tuban Pasca Sistem Kredit Semester - Atmaja, Fitriani Dina; Pribadi, Farid (Paradigma, 2021)
Interaction is an action between groups of individuals, individuals with group, groups with groups. An activity can be called an interaction when there is reciprocal communication and social contact. Social interaction starts from the family circle. Over time the interaction occurs in a broader scope such as schools. The evaluations carried out in the curriculum led to the formation of a semester credit system at various reference school. SMAN 1 Tuban is a included in the reference school for implementing SKS. SMAN 1 Tuban applies a semester credit system using UKBM learning media. The school categorizes students into two classes regular and migration (accelerated). This research is a qualitative using case study approach. The symbolic interaction that is used as an analysis knife in this study belongs to the social definition paradigm. This research tppk place at SMAN 1 Tuban. Migration and reguler class students are the subject in this study. This study uses observation, in-depth interviews, and documentation as a data collection techniques. The data that has been collected is then analyzed using a strategy developed by Miles & Huberma. Miles & Huberman categorized the analysis strategy into the processes, reduction, presentation, and conclusion. The result of this research is symbolic interaction by H. Blumer. Blumer divides his concept into five basic ideas, self concept, action, object, social interaction, and collective action. Keywoard : Semester Credit System, Student, Symbolic Interaction